Distinct neural processes are engaged in the modulation of mimicry by social group-membership and emotional expressions. (September 2015) - Rauchbauer, Birgit; Majdandžić, Jasminka; Hummer, Allan; Windischberger, Christian; Lamm, Claus
Abstract: People often spontaneously engage in copying each other's postures and mannerisms, a phenomenon referred to as behavioral mimicry. Social psychology experiments indicate that mimicry denotes an implicit affiliative signal flexibly regulated in response to social requirements. Yet, the mediating processes and neural underpinnings of such regulation are largely unexplored. The present functional magnetic resonance imaging (fMRI) study examined mimicry regulation by combining an automatic imitation task with facial stimuli, varied on two social-affective dimensions: emotional expression (angry vs happy) and ethnic group membership (in- vs out-group). Behavioral data revealed increased mimicry when happy and when out-group faces were shown. Imaging results revealed that mimicry regulation in response to happy faces was associated with increased activation in the right temporo-parietal junction (TPJ), right dorsal premotor cortex (dPMC), and right superior parietal lobule (SPL). Mimicry regulation in response to out-group faces was related to increased activation in the left ventral premotor cortex (vPMC) and inferior parietal lobule (IPL), bilateral anterior insula, and mid-cingulate cortex (MCC). We suggest that mimicry in response to happy and to out-group faces is driven by distinct affiliative goals, and that mimicry regulation to attain these goals is mediated by distinct neuro-cognitive processes. Higher mimicry in response to happy faces seems to denote reciprocation of an affiliative signal. Higher mimicry in response to out-group faces, reflects an appeasement attempt towards an interaction partner perceived as threatening (an interpretation supported by implicit measures showing that out-group members are more strongly associated with threat). Our findings show that subtle social cues can result in the implicit regulation of mimicry. This regulation serves to achieve distinct affiliative goals, is mediated by different regulatory processes, and relies on distinct parts of an overarching network of task-related brain areas. Our findings shed new light on the neural mechanisms underlying the interplay between implicit action control and social cognition.